Professional acting, political resources and patterns of investment in Rio Grande do Sul’s journalism - Petrarca, Fernanda Rios (FCL-UNESP Laboratório Editorial, 2009)
This study analyzes the recruiting patterns and professional ascending of RS journalists. One of the conditions for this professional ascending which highlights itself is composed by strategies of transformation of political resources in journalistic positions and in new definitions of the mechanisms of legitimating the professionals’ roles. The special way of relating the journalistic expertise with the political action results in the professional intervention inside public assistances and in the occupation of state institutions positions. The methodology which is used is consisted of interviews with journalists responsible by leading positions with the objective of obtaining information connected to the social, political and professional fields.